Examining the Validity of the Environmental Kuznets Curve - Karsch, Nicole Marie (Consilience, 2019)
This research essay analyzes the environmental Kuznets curve, the first hypothesis to make the correlation between economic development, environmental clean-up, and the Kuznets Curve. In essence, the EKC states that environmental quality deteriorates in the initial stages of a country’s economic development, but once a particular average income is reached that this trend will reverse and environmental degradation will begin to slow down considerably. Thus, rather than being a threat to the environment, economic growth would actually be the means to eventual environmental improvement. Although proponents of the EKC have shown some empirical evidence suggesting that rising income levels in developing countries can be advantageous rather than detrimental for the environment, this article demonstrates that there is no guarantee that economic growth will lead to an improved environment. More specifically, this essay proves that the notion that income growth by itself will be beneficial for the environment is fictitious, as a causal relationship between income and environmental quality cannot be consistently demonstrated.